Online participation modalities. Towards a conceptual delimitation (Islas, 2024)
Introduction: Although prolific, the scientific literature on online participation lacks specific definitions that conceptually delimit its different modalities, hence the purpose of this paper.Methods: A systematic bibliographic review is conducted to determine and characterize the specific actions users perform in cyberspace.Results: Participation is defined as a category closely linked to the interactive nature of the Web, as it grants new communicative roles to the audience. Now, users can collaborate with journalists in the construction of news (participatory journalism), interact with the content of cybermedia (mainly through comments on digital news), or reproduce deliberative practices in cyberspace.Conclusions: By delimiting three different participatory modalities in the virtual environment, with diverse communicative functions, an epistemological path is outlined to further explore how users appropriate digital information technologies and bring reciprocity to the communication process.
Keywords: online participation; digital news comments; user-generated content; participatory journalism